Prevalence of Kayser-Fleischer ring in patients with Wilson’s disease - Oracz, Grzegorz; Klimczak-Ślączka, Dorota; Sokołowska-Oracz, Anna; Socha, Piotr; Grałek, Mirosława; Szaflik, Jerzy; Dądalski, Maciej (Klinika Oczna / Acta Ophthalmologica Polonica, 2005)
The aim of the study was to assess prevalence of Kayser-Fleischer ring in children with Wilson's disease. 36 patients aged 7-17 years were enrolled into the study. All of them underwent ophthalmic examination by slit-lamp biomicroscopy. Kayser-Fleischer ring was found in 2 children (5.6%) – 16 years old boy and girl with liver insufficiency. In addition girl had neurological symptoms. After 2 years of treatment K-F ring wasn't detected in girl's eyes. Our data indicate that Kayser-Fleischer ring is rare in children and its absence does not exclude diagnosis of Wilson's disease.